Expanding the parameter space of the wide-pedestal QH-mode towards ITER conditions. (4th August 2020) - Chen, Xi; Burrell, K.H.; Osborne, T.H.; Barada, K.; Ernst, D.; Grierson, B.A.; McKee, G.R.; Odstricil, T.; Paz-Soldan, C.; Petty, C.C.; Rhodes, T.L.; Solomon, W.M.; et al.
Abstract: Significant parameter space expansion of the wide-pedestal quiescent H-mode (QH-mode) towards more ITER and reactor relevant conditions has been achieved in the DIII-D tokamak. Recent experiments reveal this naturally ELM-free regime can operate over a range of neutral beam injected (NBI) torque spanning from the co- to counter-Ip direction. The accessed torques completely cover the scaled ITER-equivalent applied torque range. Wide-pedestal QH-mode features an edge region where the E x B shear is lower than that of standard QH-mode and H-mode, as well as unique low- to intermediate-k turbulence and a flattening of the pedestal profiles in the low E x B shear region. Wide-pedestal QH-mode has also been extended to lower single null shaping matching ITER average triangularity. A NBI power scan at moderate density and net-zero NBI torque shows no upper power limit to wide-pedestal QH-mode while the confinement quality H98y2 increases with power. At the highest power, H98y2 reaches 1.6 and normalized pressure βN reaches 2.3 simultaneously. The wide-pedestal QH-mode also exhibits improved confinement when (1) transitioning from standard QH-mode, (2) adding core ECH power, and (3) by transitioning from LSN to DN plasma shape. Turbulence suppression by increased E x B shear inboard of the pedestal top plays an important role in all three of these observations. These recent advances make wide-pedestal QH-mode a stronger candidate for an ELM-free, high performance regime for ITER and future reactors.